Kesiapsiagaan Perawat dalam Menghadapi Bencana: Literature Review - Farly Ihsan; Cecep Eli Kosasih; Etika Emaliyawati (Faletehan Health Journal, 2022)
Nurses’ preparedness of facing disasters plays an important role in determining the success rate of disaster management. Nurses have an important role in providing nursing actions in the phase of disaster mitigation, preparedness, response, recovery and rehabilitation. The purpose of this Literature Review was to identify nurses’ preparedness in dealing with disasters. The data collection technique was by searching for articles published in 2010 – 2020 on Pubmed, Proquest, Ebsco and Google Scholar with keyword Nurse, disaster, preparedness, disaster preparedness, and disaster management. The inclusion criteria are abstract and full text, the type of search in the database with journal articles, cross-sectional study design, published in Indonesian and English, articles published from 2010 to 2020 and articles discussing the preparedness of nurses to face disasters. The article search used PRISMA flow diagram and obtained 1859 articles, but only 12 articles were included in the article analysis review. Of the 12 articles analyzed, they show that the majority of nurses were not ready in facing disasters with a range of 46.5% - 97.5%. However, 69% of nurses were interested to participate in disaster training for preparedness of self-protection. The results of the review concluded that nurses are less than optimal in dealing with disasters, so every agency must encourage the nurse preparedness training in dealing with disasters.